2021
DOI: 10.3389/fdmed.2020.617440
|View full text |Cite
|
Sign up to set email alerts
|

Response by Endodontists to the SARS-CoV-2 (COVID−19) Pandemic: An International Survey

Abstract: As SARS-CoV-2 continues to wreak havoc, health care workers are on the front lines to protect our communities. Dentists, particularly endodontists who manage dental emergencies, are engaged in high risk procedures that necessitate the modification of their treatment strategies in order to protect themselves, their staff and their patients from exposure to SARS-CoV-2. This study gathered international data from 448 endodontists to describe their awareness, their clinical care modifications, their strategies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…From the AAE mailing list, 463 responses were received giving an actual response rate of 8.3%, very similar to another recently published survey (Martinho & Griffin, 2021) but lower than 23%–24% achieved by others (Logsdon et al, 2020; Tsotsis et al, 2021). The proportion of female respondents in this study at 22% was lower than 34.4% reported in one recent international survey of endodontists (Galicia et al, 2021) but similar to 20%–21% reported in recent surveys of members of the American Association of Endodontists (Lin et al, 2015; Tsotsis et al, 2021). The overall low response rate may be due in part to the length of the survey, possible variable interest of respondents in newer endodontic technologies and lack of incentives such as vouchers or lotteries (Cho et al, 2013; Deutskens et al, 2004).…”
Section: Discussionsupporting
confidence: 77%
“…From the AAE mailing list, 463 responses were received giving an actual response rate of 8.3%, very similar to another recently published survey (Martinho & Griffin, 2021) but lower than 23%–24% achieved by others (Logsdon et al, 2020; Tsotsis et al, 2021). The proportion of female respondents in this study at 22% was lower than 34.4% reported in one recent international survey of endodontists (Galicia et al, 2021) but similar to 20%–21% reported in recent surveys of members of the American Association of Endodontists (Lin et al, 2015; Tsotsis et al, 2021). The overall low response rate may be due in part to the length of the survey, possible variable interest of respondents in newer endodontic technologies and lack of incentives such as vouchers or lotteries (Cho et al, 2013; Deutskens et al, 2004).…”
Section: Discussionsupporting
confidence: 77%
“…For example, while major professional organizations suggest a risk to dental care professionals (DCPs) of contracting COVID-19 due to the nature of their work, the extent of transmission is not documented by such organizations. 7 , 8 In contrast, some investigators have reported that COVID-19 infection rates among DCPs ranged from less than 1% to more than 15%. 7 , 8 , 9 Studies have also suggested that the majority of DCPs in many countries continued to provide care during the pandemic, but several key prevention practices (e.g., wearing N95 masks/eye protection devices or checking patient body temperature) were not followed by more than a quarter of the DCPs.…”
mentioning
confidence: 98%
“… 7 , 8 In contrast, some investigators have reported that COVID-19 infection rates among DCPs ranged from less than 1% to more than 15%. 7 , 8 , 9 Studies have also suggested that the majority of DCPs in many countries continued to provide care during the pandemic, but several key prevention practices (e.g., wearing N95 masks/eye protection devices or checking patient body temperature) were not followed by more than a quarter of the DCPs. 7 , 8 , 9 , 10 Similar to the lack of studies worldwide on DCPs’ COVID-19 infection rates, in a comprehensive review of literature, we could not find the global trends of COVID-19 vaccination preferences among DCPs.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The issue was widely discussed in the authors' work [10], which also presented the authors' technical solution serving this purpose [59]. This aspect of the endodontist's work was also highlighted in [60,61].…”
mentioning
confidence: 99%